2019
DOI: 10.3390/su11092618
|View full text |Cite
|
Sign up to set email alerts
|

Does Climate Change or Human Activity Lead to the Degradation in the Grassland Ecosystem in a Mountain-Basin System in an Arid Region of China?

Abstract: In mountain-basin systems in the arid region, grasslands are sensitive to the impacts of climate change and human activities. In this study, we aimed to resolve two key scientific issues: (1) distinguish and explain the laws of grassland ecosystem deterioration in a mountain-basin system and identify the key factors related; and (2) evaluate whether damaged grasslands ecosystem have the potential for natural revegetation. Hence, by combining spatial analysis with statistical methods, we studied the trends of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The analysis of driving forces showed that temperature was the main cause of the increasing TVDI in areas with worsening drought (i.e., with significantly and nonsignificantly increasing TVDI). Especially in areas with significantly increasing TVDI, the variation of TVDI was related to temperature in 76% of the region; while an increase in temperature will lead to an increase in transpiration and a decrease in soil moisture content, resulting in increasing drought in the study area (Yuan et al, 2017; Yan et al, 2019b; Zhang et al, 2023). Therefore, the increase in temperature was the main major reason for the aggravation of drought in the study area.…”
Section: Discussionmentioning
confidence: 93%
“…The analysis of driving forces showed that temperature was the main cause of the increasing TVDI in areas with worsening drought (i.e., with significantly and nonsignificantly increasing TVDI). Especially in areas with significantly increasing TVDI, the variation of TVDI was related to temperature in 76% of the region; while an increase in temperature will lead to an increase in transpiration and a decrease in soil moisture content, resulting in increasing drought in the study area (Yuan et al, 2017; Yan et al, 2019b; Zhang et al, 2023). Therefore, the increase in temperature was the main major reason for the aggravation of drought in the study area.…”
Section: Discussionmentioning
confidence: 93%
“…Grassland covers about 40% of the global land surface [ 1 ], provides vital ecosystem services [ 1 , 2 ], and plays an essential role in food security, biodiversity maintenance, and sustainable development [ 3 , 4 ]. However, during recent decades, half of the global grasslands were degraded due to anthropogenic and natural factors [ 2 , 3 , 5 ]. As one of the major rangeland regions in the world, the Tibetan Plateau (TP) was also experiencing serious grassland degradation [ 6 , 7 , 8 , 9 ], resulted in declines of productivity, biodiversity, soil carbon and nutrients, and related socio-economic functions [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arid areas of Northwestern China experience glacier recession, the drying-up of lakes, decreased river runoff, vegetation decline, soil salinization and land desertification [1][2][3][4]. Such ecological degradation affects social and economic development and people's livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on the above considerations, the aims of this study are to (1) analyze the relationships between farmers' land use behaviors and environmental degradation; (2) study farmers' feelings about and responses to environmental degradation; (3) put forward a new model of oasis expansion implementing land integration and realizing oasis connotation expansion; (4) guide farmers to adjust their land use behaviors to encourage the harmonious development of the social economy and the ecological environment in the Manas River Basin.…”
Section: Introductionmentioning
confidence: 99%